THE HISTORY AND TEACHINGS OF THE JADID MOVEMENT (Scientific journal of the Fergana State University, 2025)
This article examines the history of the emergence of the Jadid movement, its activities, and the stages of its development. The Jadid movement originated in the 1880s in Crimea under the leadership of Ismailbek Gasprinskiy among the Crimean Tatars, and it is analyzed how the representatives of the Jadid movement often referred to themselves as progressives, later known as Jadids. The article discusses the moral qualities of the figures in the Enlightenment movement, such as humanitarianism, patriotism, patience, gratitude, and their significance in human life, as well as the reforms and innovations in our contemporary life.